KESIAPAN SMP NEGERI 41 SEMARANG UNTUK BERKOMITMEN DAN SISTEMATIK MENGINTERNALISASIKAN NILAI LINGKUNGAN DAN SIKAP KESIAPSIAGAAN BENCANA (SWALIBA) - Setyaningsih, Wahyu; Indrayati, Ariyani (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
Swaliba is a kind of school that have commitment and use systematic method to internalize environmentalvalue and attitude of preparedness to the disaster in every school activity. There are three stages in swalib:pilot project, development, and devotion. Every stages show the school condition and readiness to implementSwaliba Program. The Semarang 41 State Yunior High School in this time preparing becoming Swalibaschool. In this stage, school need to prepare about phyisic and non physic aspect. Besed on that needed, wehaved to do research about physical aspect assesement at Semarang 41 State Yunior High School toimplement Swaliba and than rewrite that report as an article below.The research method is survey, thanobservation the condition and compared to the physical standart measurement as disaster-resistantstructure. The result of the studi is show that Semarang 41 State Yunior High School is ready to internalizethe environtment value. At the other side, physically, the buiding at Semarang 41 State Yunior High School issafe from thunder-strom or hurricane and also earthquake but do not yet ready to facing a fire hazard. At theother side, Semarang 41 State Yunior High School in non-physic aspect consider to be quite ready toimplement Swaliba Program gradually.